2013
DOI: 10.1038/onc.2013.446
|View full text |Cite
|
Sign up to set email alerts
|

The age- and shorter telomere-dependent TERT promoter mutation in follicular thyroid cell-derived carcinomas

Abstract: Telomerase activation through induction of its catalytic component telomerase reverse transcriptase (TERT) expression is essential for malignant transformation. TERT promoter mutations namely C228T and C250T that stimulate TERT transcription and telomerase activation have recently been identified in many human malignancies. We thus determined these mutations and their biological and clinical implications in thyroid carcinomas in the present study. The TERT promoter was sequenced in 10 thyroid cancer cell lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

35
266
3
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 217 publications
(315 citation statements)
references
References 28 publications
35
266
3
4
Order By: Relevance
“…In a large series of 469 follicular cell-derived thyroid carcinomas (FCDTC), TERT promoter mutations were found in 7.5 % of PTC, 17.1 % of FTC, 29.0 % of poorly differentiated thyroid carcinomas (PDTC) and 33.0 % of anaplastic thyroid carcinomas (ATC) [80]. This stepwise increase in the frequency of TERT promoter mutations from well to poorly differentiated and undifferentiated carcinomas was also reported in other studies [66,74] (Table 2). TERT promoter mutations were not detected in normal thyroid tissue, benign lesions or medullary thyroid carcinoma (MTC).…”
Section: Telomerase Promoter Mutations In Thyroid Carcinomassupporting
confidence: 76%
See 3 more Smart Citations
“…In a large series of 469 follicular cell-derived thyroid carcinomas (FCDTC), TERT promoter mutations were found in 7.5 % of PTC, 17.1 % of FTC, 29.0 % of poorly differentiated thyroid carcinomas (PDTC) and 33.0 % of anaplastic thyroid carcinomas (ATC) [80]. This stepwise increase in the frequency of TERT promoter mutations from well to poorly differentiated and undifferentiated carcinomas was also reported in other studies [66,74] (Table 2). TERT promoter mutations were not detected in normal thyroid tissue, benign lesions or medullary thyroid carcinoma (MTC).…”
Section: Telomerase Promoter Mutations In Thyroid Carcinomassupporting
confidence: 76%
“…The majority (about 80 %) of mutated cases presented the −124G>A mutation. In PTC, TERT promoter mutations were significantly more frequent in BRAF-mutated tumours than in BRAF wild-type tumours [74,75,80,121]. The TERT promoter mutations were associated with increased mRNA expression, and this increase was particularly pronounced in tumours harbouring both BRAF and TERT promoter mutations [121].…”
Section: Telomerase Promoter Mutations In Thyroid Carcinomasmentioning
confidence: 96%
See 2 more Smart Citations
“…The correlation between TERT promoter mutations and older patient age has been shown in glioblastoma, medulloblastoma, 20 papillary thyroid carcinoma (445 years old), 27 and urothelial carcinoma of the urinary bladder (450 years old). 28 In contrast, a previous study by Wu et al showed that no relationship could be found between patient age and TERT promoter mutations.…”
Section: Discussionmentioning
confidence: 97%